واقع خدمات الصحة المدرسية في التعليم االبتدائي العام بمدينة بنغازي كما يدركها المشرفون عليها - مخلوف عيسى رمضان محمد (Scientific Journal of University of Benghazi, 2021)
The study aimed to identify the reality of school health services (preventive and curative) in primary schools in the city of Benghazi as perceived by their supervisors, and to know the statistically significant differences in the reality of school health services (preventive - curative) that may be attributed to the variables of gender, length of service and training courses for supervisors. Therefore, the researchers adopted the descriptive analytical approach, and the study population consisted of teachers who supervise school health in the general primary education in the city of Benghazi, whose number is (313) supervisors and supervisors. A sample of primary education schools distributed among the three educational services offices was selected to monitor the education of Benghazi, at an amount of 50% of the schools within each office, and then a stratified random sample was selected with a number of (150) supervisors and supervisors at 47% of the study population, and a questionnaire was used Prepared by researchers as a tool for collecting information related to the subject of the study, and the study resulted in a set of results, including: The most important preventive services provided in primary schools in Benghazi (refreshing and seasonal vaccinations and upon entering schools, flyers and posters to prevent diseases, monitoring the school canteen and following up on the requirements health in it), As for the most important treatment services (initial examination of new students, it also provides first aid for emergency cases, medical examination of teachers in each academic year). The results also showed that there are no statistically significant differences in school health services according to the variables of type and service duration, and there are statistically significant differences in school health services according to the variable of training courses in the areas of preventive services and the total degree, while there are no differences for the same variable in the field of services therapeutic.